Penerapan E-LKPD Asam Basa pada Isu-isu Sosial Ilmiah untuk Meningkatkan Kemampuan Berpikir Kritis dan Motivasi Belajar - Faira Yovanie; Roza Linda; Lenny Anwar (Postgraduate, University of Mataram, 2025)
This research is motivated by the low critical thinking skills of students in chemistry learning. This is indicated by students who have not been trained in analyzing a problem and a lack of involvement, so that students are not motivated to learn. Students need effective teaching materials to be actively involved in analyzing problems and motivating learning, so that E-LKPD based on Socio-Scientific Issues is expected to be a learning innovation. This study aims to measure the effectiveness of E-LKPD based on Socio-Scientific Issues in acid-base learning on critical thinking and student learning motivation. E-LKPD is presented via the web Liveworksheets as an interactive medium. The type of research used is a quasi-experiment with a nonequivalent group pretest-posttest research design. The study was conducted in class XI IPA 8 and XI IPA 1 SMAN 4 Pekanbaru consisting of 90 students. Data analysis used the Normality test, t-test, and N-gain test. The results of the analysis for critical thinking obtained an N-gain of 0.6586 in the control class and 0.7509 in the experimental class. Meanwhile, for learning motivation, the N-gain obtained was 0.2537 in the control class and 0.4548 in the experimental class. Furthermore, the results of the t-test showed that there was a significant difference between critical thinking skills and learning motivation in the control class and the experimental class. Critical thinking skills and learning motivation have a positive relationship as evidenced by the sig. value < 0.05 with a Pearson correlation value of 0.419, thus E-LKPD based on Socio-Scientific Issues is effective in improving critical thinking skills and learning motivation in acid-base learning.